ABOUT THE MAIN TASKS OF TEACHING GEOMETRY AT THE SECONDARY SCHOOL - Mamatov, Jasur; Qahhorov, Muhriddin; Parmanov, Abulqosim; Fayzullaev, Sherzod (Журнал математики и информатики, 2021)
Annotation: In this paper we investigated the main tasks of teaching the geometry subject at school, and therefore the developing mathematical and logical sophism of students and their stages of spatial imagination.